RETRACTED: Transmission diagnostics of single-rotor helicopters - Reshenkin Andrey; Kochkovaya Natalia; Ezdanyan Valerik (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001